2022
DOI: 10.3390/cancers15010284
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Baseline Proton Pump Inhibitors, Immune Checkpoint Inhibitors, and Chemotherapy: A Systematic Review with Network Meta-Analysis

Abstract: (1) Although emerging evidence suggests that proton pump inhibitor (PPI)-induced dysbiosis negatively alters treatment response to immune checkpoint inhibitors (ICIs) in cancer patients, no study systematically investigates the association between PPIs, ICIs, and chemotherapy; (2) Cochrane Library, Embase, Medline, and PubMed were searched from inception to 20 May 2022, to identify relevant studies involving patients receiving ICIs or chemotherapy and reporting survival outcome between PPI users and non-users.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Considering the inconsistent findings, the antitumor effect of PPIs is more likely to be derived from a combination of factors such as cancer type and stage, as well as concomitant drug therapy [48]. Thus, until a clear pattern emerges, caution should be applied when administering PPIs and systemic antitumor therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the inconsistent findings, the antitumor effect of PPIs is more likely to be derived from a combination of factors such as cancer type and stage, as well as concomitant drug therapy [48]. Thus, until a clear pattern emerges, caution should be applied when administering PPIs and systemic antitumor therapy.…”
Section: Resultsmentioning
confidence: 99%
“…More broadly, the hallmark inversion of the pH gradient in cancer cells suggest that inhibitors of proton pumps and exchangers may improve chemosensitivity of tumours 52 . However, trials have returned mixed results with adverse patient outcomes reported when proton pump inhibitors were combined with kinasetargeting drugs or immune-checkpoint inhibitors 53,54 . While this is in part due to drug-drug interactions 55 , an improved understanding of the association between increased pHi and kinase signal regulation of cancer progression appears to be necessary to optimize pHi targeting as a therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, drug-drug interaction between ICIs, antibiotics (ATB), and proton-pump inhibitors (PPI) have been raised. The majority of publications are retrospective studies, but a meta-analysis seems to demonstrate a negative impact of this medication on ICIs' outcomes [136,137]. The decrease in overall survival and progression-free survival by ATB and PPI would probably result from the balance between the gut microbiota and immune checkpoint inhibitors.…”
Section: The Role Of Microbiotamentioning
confidence: 99%